Improvement of legal acts regulating representation on someone’s behalf in civil proceedings - Zhamburbayeva, S. (Bulletin of the Karaganda University “Law Series”, 2022)
In modern society, the current century is associated with a new stage of development – the state’s gaze is riveted to many areas, including the legal one, to which numerous changes and additions are being made. However, in addition to the intensive development of legal technologies, there are internal problems of regulating the sphere of professional legal assistance, including the conclusion of a contract between a representative and a representative, despite the active legal transformation of the activities of lawyers and legal consultants. Practitioners and theorists discuss the issues of paying well-deserved remuneration to a lawyer, a legal consultant under a contract for the provision of legal assistance. Particular attention is paid to a specific form of payment for legal services, called “success fee”. In addition, the author of the study considers no less controversial the problem of ensuring professional secrecy, which requires additional regulation by the legislator, especially when traditional practices fade into the background, and society and business rely on IT technologies. Also, foreign legislative acts are studied to analyze the identified legal gaps, and based on this, a way to eliminate them is proposed to modernize the activities carried out by lawyers and legal consultants in the process of concluding a contract and providing legal assistance for representation in court.